Clothes retrieval based on ResNet and cluster triplet loss. Issue 9 (May 2023) - Li, Changshun; Peng, Chen; Yao, Li; Fu, Qiming; Dai, Yu; Yang, Junyan
Clothes image retrieval is a task that retrieves exact or very similar clothes from a large clothes image gallery according to a given query image. The high deformability of clothes and similar designs make clothes retrieval very difficult. Convolutional neural networks perform well in the feature extraction field, but cannot extract sufficiently fine-grained features for clothes retrieval tasks. Therefore, a model based on ResNet was designed in this article, with several improvements made to it to ensure better feature discrimination. On the other hand, pair-based loss functions that are commonly used in image retrieval suffer from insufficient discrimination ability, difficulty in convergence, and time-consuming during training. Cluster triplet loss function is proposed in this article, which reduces the computational complexity in the training phase and enables the model to have a certain ability to resist noise labels. Experiments are completed on In-shop clothes retrieval benchmark and Consumer-to-shop clothes retrieval benchmark in Deepfashion, and stanford online products (SOP) to supplement. Our method can have Recall@1 improvements of 1.3–1.7% on all three datasets, surpassing the latest state-of-the-art methods.